Influence of Managerial Ownership, Board Independence, and Leverage on Financial Performance in the Financial Sector - Francis; Trisnawati, Estralita (E-Jurnal Akuntansi, 2025)
This study examines the impact of managerial ownership, independent commissioners, and leverage on the financial performance of financial sector firms in Indonesia, with the growth of Bank Indonesia's interest rates as a moderating variable. A quantitative research approach is employed, utilizing secondary data from the financial statements of financial sector companies listed on the Indonesia Stock Exchange (IDX). The analysis is conducted using Moderated Regression Analysis (MRA). The findings indicate that managerial ownership and independent commissioners positively influence financial performance, while leverage exhibits a nonlinear relationship with financial performance. Additionally, the growth of Bank Indonesia's interest rates moderates the relationship between leverage and financial performance, reinforcing specific interactions between the independent variables and firm performance. These results provide insights into the role of corporate governance mechanisms and capital structure in shaping financial outcomes within Indonesia’s financial sector.